GAYA BAHASA FIGURATIF DALAM NOVEL KABUT DAN MIMPI KARYA BUDI SARDJONO - Nama, I Ketut (Prosiding Seminar Nasional Bahasa Ibu; Vol 2 No 1 (2025): Prosiding Seminar Nasional Bahasa Ibu 2024/2025, 2025)
The novel Kabut dan Mimpi ( Fog and Dream ) tells the story of the main character, Kardi, a sand miner at Kali Boyong. One night, he dreams of meeting Mbah Gadung Melati, who predicts that Kardi will one day become a high-ranking official. Kardi then fights for his fate alongside his friends by protesting and demonstrating against the foreman who supervises their work at Kali Boyong. Kardi is eventually captured, imprisoned, and thrown into a ravine. However, his life is saved, and he continues to fight for his destiny. Eventually, Kardi confronts Mbah Nyai Gadung Melati, a supernatural being residing at the foot of Mount Merapi, regarding the prophecy in his earlier dream. The novel Kabut dan Mimpi ( Fog and Dream ) is written in Indonesian, with Javanese words and expressions interspersed throughout. This paper aims to analyze the use of figurative language in the novel Kabut dan Mimpi ( Fog and Dream ). The data is analyzed qualitatively using a descriptive-analytical method. Based on the analysis, it is found that several types of figurative language are used, such as figures of speech, idioms, and proverbs. The figures of speech frequently encountered include simile, repetition, personification, synesthesia, bombast, hyperbole, and paradox. Additionally, several idioms and proverbs are also used. The use of figurative language is intended to emphasize meaning and create specific effects in the storytelling.